Problems of a longtime strawberry growing in one plot - Albinas Lugauskas; Jūratė Repečkienė; Nobertas Uselis; Albina Birutė Rašinskienė (Acta Scientiarum Polonorum: Hortorum Cultus, 2003)
Long term investigations revealed that cultivation of strawberries (Fragaria magna Thuill.) for 10 years continuously in one plot reduces their vitality: the number of the produced runners decreases by 41%, of leaves - by 30%, form only 28% of inflorescence, the yield reduces by 50% in comparison with strawberries grown for two years in a new plot. Evident decline in the vitality and productivity of strawberries was detected during 4th-6th years of cultivation. Unequal reaction of the tested cultivars upon the durability of cultivation was noticed; strawberries of the cultivar "Senga Sengana" reacted slightly, while the ones of the cultivar "Nida" - strongly. It is related with different sensibility of these cultivars towards the disease agents of root rots. It was determined that long-term cultivation of the Fragaria genus plants results in the accumulation of the parasitic fungi propagules in soil: Ascochyta fragaricola, Cercospora fragariae, Fusarium oxysporum, F. solani, Perenospora fragariae, Phytophthora cactorum, Pythium intermedium, P. ultimum, Plasmodiophora brassicae, Sclerotium rolfsii, Verticillium alboatrum. Therefore, cultivation of strawberries in the same plot for longer time increases the phytopathogenic potential of soil, and short interval (1-2 years) between planting has little significance upon it. The second reason for low productivity of strawberries cultivated for a long in one plot is soil tiredness caused by fungi, synthesising and excreting into surrounding toxic secondary metabolites, widespread in the rhizosphere, especially those belonging to the Penicillium genus: P. janthinellum, P. verruculosum var. verrucosum, P. canescens, P. spinulosum.